Manufacturing method of high ionic conducting solid electrolyte for all-solid battery
Patent Information
- Application Number
- KR1020230144546
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2043-10-26
Smart Images

Figure 112023117844789-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a highly ion-conducting solid electrolyte for all-solid-state batteries, and more specifically, to a Li that is applicable as a highly ion-conducting solid electrolyte for all-solid-state batteries. 3x La2 / 3-x□1 / 3-2x This invention relates to a manufacturing method that can effectively and significantly improve the ionic conductivity of a TiO3 composition. Background Technology
[0002] Lithium-ion rechargeable batteries possess the advantages of high energy density, a low self-discharge rate, and excellent charge-discharge cycles. However, since conventional lithium-ion rechargeable batteries use liquid electrolytes, they can easily ignite when exposed to moisture in the air, and safety issues such as thermal runaway have always been seriously raised.
[0003] Therefore, to address this, all-solid-state batteries utilizing solid electrolytes currently under development are highly promising, as they offer exceptionally high safety while also possessing advantages such as high power output, long lifespan, and simple manufacturing processes. These all-solid-state batteries generally consist of a cathode, a solid electrolyte layer, and a negative electrode; since the solid electrolyte is primarily composed of inorganic materials, high ionic conductivity is required to enhance lithium-ion transfer efficiency.
[0004] In particular, the above-mentioned solid electrolyte is generally advantageous in that it has a perovskite material composition with an ABO3 crystal structure, where alkali metals and alkaline earth metals are present at the A site and transition metals are present at the B site. Known compositions include Li 3x La2 / 3-x□1 / 3- 2x TiO3 (so-called "LLTO") (where 0 <x<0.16, □는 공공이다)이 있다. 이 LLTO는 그의 결정구조에서 A자리에 Li + Wow La 3+ This partially occupies the space, and in position B, Ti 4+ is located.
[0005] However, the grain Li ion conductivity of this LLTO solid electrolyte at room temperature is ~10 -3 Although it is on the high side among oxide solid electrolytes at S / cm, the ionic conductivity at grain boundaries (or interfaces) is ~10 -5 Since the ionic conductivity is very low at S / cm, the total ionic conductivity of the LLTO is ultimately also ~10 -5 It ends up being only at the level of S / cm.
[0006] Accordingly, there have been attempts to improve the conductivity of LLTO solid electrolytes by controlling the amount of vacancies (□) through doping or by substituting elements at the A and B sites in the ABO3 perovskite structure.
[0007] As an example, if La is doped with Sr (La0 .57-2x / 3Sr x Li0 . It is reported that the size of the Li ion channel and the arrangement of A-site ions and vacancies change, and consequently, the ion conductivity increases.
[0008] Also, as another example, if Ti in the B position is doped with Ta, Ta with a +5 value 5 + Research results have also been reported indicating that the overall ionic conductivity increases because ions weaken the Li-O bond, thereby improving the mobility of Li ions. Prior art literature
[0009] 1. Published Patent Application No. 2017-0034581 (March 29, 2017)
[0010] 2. Published Patent Application No. 2019-0078804 (July 5, 2019)
[0011] 3. You Na Lee et al., Thin Solid Films, Vol.579, 2025.03.31, pp.75~80
[0012] 4. Yubin Zhang et al., Journal of The Electrochemical Society, 2020 167 080516 The problem to be solved
[0013] The present invention relates to Li applicable as a highly ion-conductive solid electrolyte for all-solid-state batteries. 3x La 2 / 3-x□1 / 3-2x The purpose is to provide a manufacturing method that can effectively improve the ionic conductivity of a TiO3 composition. means of solving the problem
[0014] Li according to the present invention for solving the above problem 3x La2 / 3-x□1 / 3- 2x TiO3(at this time, 0 <x<0.16이고 □는 공공이다; 이하 'LLTO'라 한다) 조성물의 제조방법은 다음 단계 (i)~(iii)를 포함한다:
[0015] (i) LiCO3, La2O3 A step of preparing each starting material of and TiO2 and mixing them together to produce a mixed powder, wherein the TiO2 starting material is prepared to have a complex crystalline phase in which anatase phase and rutile phase are mixed together;
[0016] (ii) a step of solid-state synthesis of the above mixed powder into the powder of the above LLTO composition by calcining the above mixed powder in a temperature range of 900 to 1200℃; and
[0017] (iii) A step of forming a solid solution by molding the powder of the solid-state synthesized LLTO composition into a predetermined shape and sintering it.
[0018] At this time, optionally, the composite crystal phase of the TiO2 starting material in step (i) may have a phase fraction of anatase phase:rutile phase in the range of 90.5:9.5 to 17.5:82.5.
[0019] Additionally, optionally, preparing the TiO2 starting material in step (i) to have a composite crystal phase in which the anatase phase and the rutile phase are mixed may include a step of heat-treating the anatase TiO2 as a starting material at 800 to 850°C. Additionally, optionally, the anatase TiO2 The particle size of the powder may be 80 nm ± 10%. Additionally, optionally, the heat treatment may be performed under an atmospheric environment. Additionally, optionally, the heat treatment may be performed within a range of 1 to 9 hours.
[0020] Additionally, optionally, in step (iii), the sintering may be performed in a temperature range of 1150 to 1250°C.
[0021] Additionally, optionally, in step (iii), the solid solution is 1.18 × 10⁻⁶ -3 S / cm to 1.69×10 -3 It can have a grain boundary ionic conductivity of S / cm.
[0022] Additionally, optionally, by treating the TiO2 starting material in step (i) to have a composite crystal phase in which the anatase phase and the rutile phase are mixed with each other, the expression of one or more of the unreacted phase and the secondary phase in the LLTO composition synthesized in the solid phase in step (iii) can be suppressed. Effects of the invention
[0023] The present invention improves ion conductivity by using a composite of the starting material TiO2 in anatase and rutile crystal structures, without the need for conventional doping with elliptical elements, thereby utilizing Li 3x La2 / 3-x□1 / 3- 2xSignificantly enhanced ion conductivity characteristics can be achieved by synthesizing and manufacturing a TiO3 composition. Consequently, when applied as a solid electrolyte for all-solid-state batteries, the transfer efficiency of internal lithium ions can be greatly improved. Furthermore, since the present invention does not require doping with other elements, the manufacturing process is simplified and manufacturing costs can be effectively reduced. Brief explanation of the drawing
[0024] FIG. 1 is a flowchart illustrating a method for manufacturing LLTO and measuring dielectric properties according to an embodiment of the present invention. Figures 2a and 2b are X-ray diffraction (XRD) results of anatase-rutile composite TiO2 powder obtained by heat treatment at 800 to 850°C in an embodiment of the present invention while varying the temperature and time in a holding range of 1 to 9 hours, and Figure 2b is an enlarged view of the 24 to 29° range in Figure 2a. FIG. 3 is a graph showing the change in the anatase phase:rutile phase fraction obtained in the embodiments of the present invention of FIG. 2a and 2b. Figure 4a is the X-ray diffraction (XRD) result of LLTO powder synthesized in a solid state at a temperature range of 1000 to 1200°C by mixing 100% anatase TiO2 powder, not anatase-rutile composite TiO2 powder, with LiCO3, La2O3, and TiO2 powders as Comparative Example 1 of the present invention, and Figure 4b is the X-ray diffraction (XRD) result of LLTO powder synthesized in a solid state by mixing and heat-treating 100% rutile TiO2 powder, not anatase-rutile composite TiO2 powder, as Comparative Example 2 of the present invention, in the same manner as Figure 4a. Figures 5a and 5b are X-ray diffraction (XRD) analysis results of LLTO powder synthesized in solid state according to embodiments of the present invention. Figure 6 is a scanning electron microscope (SEM) image of LLTO powder synthesized in solid phase in comparative examples and embodiments of the present invention, respectively, according to the solid phase synthesis temperature. Figures 7a and 7b are graphs showing the change in ionic conductivity measured by sintering disk specimens composed of LLTO powder synthesized in the solid state at 1100°C in an embodiment of the present invention, observed according to the TiO2 composition used as the starting material and the calcination temperature. Here, as shown on the x-axis of this graph, the TiO2 starting material compositions are, from left to right: 100% anatase-phase TiO2 (Comparative Example 1), anatase-rutile composite TiO2 (Examples 1 and 2, i.e., Composite #1 and #2 in Table 1), and 100% rutile-phase TiO2. The composition (Comparative Example 2) is changed sequentially, and the firing temperature is changed to 1150℃, 1200℃, and 1250℃. In particular, FIG. 7a shows the change in grain boundary ionic conductivity, and FIG. 7b shows the change in total ionic conductivity. Specific details for implementing the invention
[0025] The aforementioned Li, a high ion-conducting solid electrolyte for all-solid-state batteries 3x La 2 / 3-x□1 / 3-2x In the composition of TiO3 (: LLTO), the present invention discloses that when LLTO is synthesized using a starting material, TiO2, which is composited into an anatase phase and a rutile phase crystal structure without the need to dope other elements as in the conventional method to improve ionic conductivity, the LLTO exhibits significantly higher ionic conductivity compared to the aforementioned conventional doped LLTO.
[0026] In particular, as will be described later, the LLTO produced according to the present invention has a grain boundary ionic conductivity (or interfacial ionic conductivity) of approximately 1.69 × 10⁻⁶. -3 The theoretical grain boundary ionic conductivity of LLTO, as S / cm, is approximately 1×10⁻⁶ -3 It is implemented with a value greater than S / cm, and the total ionic conductivity is approximately 4.52 × 10⁻⁶. -5 The theoretical total ionic conductivity of LLTO is approximately 7×10⁻⁶ S / cm. -5 It is approximately 65% of S / cm.
[0027] In this invention, the anatase-rutile composite TiO2 is used as a precursor having an anatase-rutile phase fraction in the range of approximately 90.5:9.5 to 17.5:82.5.
[0028] That is, in one embodiment of the present invention, such composite phase TiO2 can be used as a powder according to the oxide mixing method to form an LLTO mixed powder together with other starting materials, such as LiCO3 and La2O3, and then LLTO can be synthesized in a solid state at a temperature range of approximately 1000 to 1200°C. As will be described later, it is confirmed that a uniform LLTO synthesized powder is produced, which has no unreacted phase or secondary phase in the crystal structure and excellent angularity of the powder in the microstructure.
[0029] In addition, in one embodiment of the present invention, the solid-state synthesized LLTO powder may be compressed, for example, into a bulk form and then sintered and dissolved at a temperature range of approximately 1150 to 1250°C, in which case, as will be described later, approximately up to 1.69 × 10⁻⁶ -3 A very high level of grain boundary ionic conductivity of S / cm is obtained.
[0030] FIG. 1 is a flowchart illustrating a method for manufacturing LLTO and measuring dielectric properties according to an embodiment of the present invention. Hereinafter, the method for manufacturing LLTO according to the present invention will be described in detail for each process with reference to the drawings.
[0032] Anatase-rutile complex TiO2 2 Powder manufacturing
[0033] In one embodiment of the present invention, anatase-rutile composite TiO2 powder can be produced by using anatase TiO2 as a starting material, heating it in a furnace at a rate of 1°C / min, maintaining it at approximately 800 to 850°C for 1 to 9 hours, and varying the temperature and time (S100 of FIG. 1). As an example, the particle size of the anatase TiO2 powder, which is the starting material, may be approximately 80 nm ± 10%, and very preferably approximately 80 nm. Also, as an example, the heat treatment may be performed in an atmospheric environment.
[0034] FIGS. 2a and 2b are X-ray diffraction (XRD) results of anatase-rutile composite TiO2 powder obtained by heat treatment at 800 to 850°C for 1 to 9 hours while varying the temperature and time in the embodiment of the present invention, and FIG. 2b is an enlarged view of the 24 to 29° section in FIG. 2a. In addition, FIG. 3 is a graph showing the change in the anatase phase:rutile phase fraction obtained in this embodiment.
[0035] Referring to Figures 2a and 2b and Figure 3, it is confirmed that anatase-rutile composite TiO2 powder with phase fractions changing according to various heat treatment temperatures and time variations is obtained.
[0036] Table 1 summarizes the phase fractions of Composite #1 and Composite #2, which are manufactured using LLTO as embodiments of the present invention. Composite #1 is a powder heat-treated by holding at 800°C for 5 hours (indicated as (a) in FIG. 2a-2b and FIG. 3), and Composite #2 is a powder heat-treated by holding at 850°C for 9 hours (indicated as (b) in FIG. 2a-2b and FIG. 3).
[0037] Phase fraction of anatase-rutile composite TiO2 powder of the embodiments of the present invention manufactured by heat treatment Anatase Rutile Composite #1 90.5 9.5 Composite #2 17.5 82.5
[0039] Solid-state synthesis - LLTO Manufacturing of synthetic powder
[0040] In one embodiment of the present invention, the previously prepared anatase-rutile composite TiO2 powder and LiCO3, La2O3, and TiO2 powders are weighed and mixed (S110 to S120 in FIG. 1) to prepare a mixed powder, and then LLTO can be synthesized in a solid state at a temperature range of approximately 900 to 1200°C, preferably 1000 to 1200°C (S130 in FIG. 1). As an example, Table 2 below shows the mixing ratio and weight ratio weighed in the mixed powder.
[0041] Mixing ratio of LLTO mixed powder Li La Ti O Mixing ratio 0.33 0.56 1.00 3.00 weight ratio 14.58 98.59 86.83
[0042] First, Fig. 4a is the X-ray diffraction (XRD) result of LLTO powder synthesized in a solid state at a temperature range of 1000 to 1200°C by mixing 100% anatase TiO2 powder, not anatase-rutile composite TiO2 powder, with LiCO3, La2O3, and TiO2 powders as Comparative Example 1 of the present invention, and Fig. 4b is the X-ray diffraction (XRD) result of LLTO powder synthesized in a solid state by mixing and heat-treating 100% rutile TiO2 powder, not anatase-rutile composite TiO2 powder, as Comparative Example 2 of the present invention, in the same manner as Fig. 4a.
[0043] Looking at Fig. 4a, it is confirmed that some unreacted phases exist in the LLTO powder synthesized in solid state using 100% anatase TiO2 powder as a starting material in Comparative Example 1. Additionally, looking at Fig. 4b, it is confirmed that some secondary phases exist in the LLTO powder synthesized in solid state using 100% rutile TiO2 powder as a starting material in Comparative Example 2.
[0044] Meanwhile, Figures 5a and 5b show the X-ray diffraction (XRD) results of LLTO powder synthesized in solid state according to embodiments of the present invention.
[0045] That is, Fig. 5a is the XRD result of LLTO powder synthesized in a solid state at each temperature in the temperature range of 1000 to 1200°C by mixing TiO2 powder with an anatase-rutile composite (Composite #1 in Table 1 above, i.e., anatase phase:rutile phase = 90.5:9.5) as Example 1 of the present invention with LiCO3, La2O3, and TiO2 powders. Fig. 5b is the XRD result of LLTO powder synthesized in a solid state by mixing and heat-treating TiO2 powder with an anatase-rutile composite (Composite #2 in Table 1 above, i.e., anatase phase:rutile phase = 17.5:82.5) as Example 2 of the present invention.
[0046] Looking at Figures 5a and 5b, it is confirmed that all LLTO powders synthesized in solid phase according to Examples 1 and 2 are synthesized as uniform LLTO without unreacted phases or secondary phases.
[0047] In addition, FIG. 6 is a scanning electron microscope (SEM) image of LLTO powder synthesized in solid phase in Comparative Examples 1 and 2 and Examples 1 and 2 of the present invention according to the solid phase synthesis temperature.
[0048] Referring to FIG. 6, it is confirmed that, compared to the case where 100% anatase or 100% rutile TiO2 powder was applied as in the comparative examples above, when anatase-rutile composite TiO2 powder was applied according to the embodiments of the present invention above, no unreacted phases or secondary phases that occurred in the comparative examples are found at all.
[0049] That is, by applying the anatase-rutile composite TiO2 powder according to the present invention, unreacted phases and secondary phases that may occur during the synthesis process can be effectively suppressed, and in particular, as shown in FIG. 6, it can be seen that the angularity of the powder is excellent.
[0051] Measurement and Evaluation of Ion Conductivity of LLTO Bulk Specimens
[0052] In this section, the ion conductivity of the LLTO powder synthesized in solid state as described above is measured and evaluated after sintering. In one embodiment, the LLTO powder is compressed and molded into a bulk, such as a disc shape, to produce a specimen, and then the specimen is sintered at a temperature range of approximately 1150 to 1250°C, after which the ion conductivity of the sintered specimen can be evaluated.
[0053] FIGS. 7a and 7b are graphs showing the change in ionic conductivity measured by sintering disk specimens composed of LLTO powder synthesized in the solid state at 1100°C in an embodiment of the present invention, observed according to the TiO2 composition applied as a starting material and the calcination temperature, wherein the TiO2 starting material compositions are 100% anatase-phase TiO2 (Comparative Example 1), anatase-rutile composite-phase TiO2 (Examples 1 and 2, i.e., Composite #1~#2 in Table 1), and 100% rutile-phase TiO2 The composition (Comparative Example 2) is changed, and the firing temperature is changed to 1150℃, 1200℃, and 1250℃, and in particular, FIG. 7a shows the change in grain boundary ionic conductivity and FIG. 7b shows the change in total ionic conductivity, respectively.
[0054] Referring to Fig. 7a, in the case of the specimen sintered at 1200°C using LLTO powder synthesized in the solid state at 1100°C using the anatase-rutile composite TiO2 powder of Example 2 (Composite #2 in Table 1), the maximum is approximately 1.18 × 10⁻⁶ -3 S / cm to 1.69×10 -3 It can be confirmed that very high grain boundary ionic conductivity is exhibited in S / cm. Furthermore, due to this excellent grain boundary ionic conductivity, as shown in Fig. 7b, it is 4.52×10 -5 This leads to the overall ionic conductivity of the specimen, which is excellent as S / cm.
[0055] Thus, the grain boundary ionic conductivity of the LLTO produced according to the present invention is the theoretical grain boundary ionic conductivity of LLTO (approximately 1×10⁻⁶). -3S / cm) and the grain boundary ionic conductivity (approx. 1.26 × 10⁻⁶) of the aforementioned conventional Nd-doped LLTO -3 It is realized with a value significantly larger than S / cm. Furthermore, accordingly, its overall ionic conductivity is also excellent, compared to the theoretical overall ionic conductivity of LLTO, which is approximately 7×10⁻⁶. -5 It approaches approximately 65% of S / cm (comparison is impossible as the total ionic conductivity of conventional Nd-doped LLTO has not been published).
[0056] As examined above, the present invention enables the synthesis and production of LLTO using a composite of anatase and rutile crystal structures of the starting material TiO2, without the need to dope other elements as in the conventional method to improve ion conductivity, thereby achieving much better ion conductivity than in the conventional method. Accordingly, the manufacturing process can also be simplified and manufacturing costs can be effectively reduced.
[0057] In the embodiments of the present invention described above, it is obvious to those skilled in the art that there may be some variation within a normal margin of error depending on powder characteristics such as the average particle size, distribution, and specific surface area of the composition powder, as well as the purity of the raw material, the amount of impurities added, and the sintering conditions.
[0058] In addition, preferred embodiments of the present invention are disclosed for illustrative purposes only, and anyone skilled in the art can make various modifications, changes, and additions within the spirit and scope of the present invention, and such modifications, changes, and additions should be considered to fall within the scope of the claims.
Claims
Claim 1 Li 3x La 2 / 3-x□1 / 3-2x TiO3(at this time, 0 <x<0.16이고 □는 공공이다; 이하 'LLTO'라 한다) 조성물의 제조방법에 있어서,(i) LiCO3, La2O3및 TiO2의 각 출발물질을 준비하고 서로 혼합하여 혼합분말을 제조하되, 상기 TiO2출발물질은 아나타제상 및 루틸상의 복합결정상을 갖도록 준비하는 단계;(ii) 상기 혼합분말을 900~1200℃의 온도범위에서 하소하여 상기 LLTO 조성물의 분말로 고상합성하는 단계; 및(iii) 고상합성된 상기 LLTO 조성물의 분말을 사전 결정된 형태로 성형하고 소결함으로써 고용체를 형성하는 단계를 포함하는 것을 특징으로 하는 LLTO 조성물의 제조방법. Claim 2 A method for preparing an LLTO composition according to claim 1, characterized in that, in step (i), the composite crystal phase of the TiO2 starting material has a phase fraction of anatase phase:rutile phase in the range of 90.5:9.5 to 17.5:82.
5. Claim 3 A method for preparing an LLTO composition according to claim 1 or 2, wherein in step (i), the preparation of the TiO2 starting material to have a composite crystal phase in which the anatase phase and the rutile phase are mixed with each other includes the step of heat-treating the anatase TiO2 as a starting material at 800 to 850°C. Claim 4 In paragraph 3, the above anatase TiO2 A method for preparing an LLTO composition characterized by the powder particle size being 80 nm ± 10%. Claim 5 A method for manufacturing an LLTO composition according to claim 3, characterized in that the heat treatment is performed under an atmospheric environment. Claim 6 A method for manufacturing an LLTO composition according to claim 3, characterized in that the heat treatment is performed within the range of 1 to 9 hours. Claim 7 A method for manufacturing an LLTO composition according to claim 1 or 2, characterized in that, in step (iii), the sintering is performed in a temperature range of 1150 to 1250°C. Claim 8 In claim 1 or 2, in step (iii), the solid solution is 1.18 × 10⁻⁶ -3 S / cm to 1.69×10 -3 A method for preparing an LLTO composition characterized by having a grain boundary ion conductivity of S / cm. Claim 9 A method for preparing an LLTO composition according to claim 1 or 2, characterized in that, in step (i), the TiO2 starting material is treated to have a composite crystal phase in which the anatase phase and the rutile phase are mixed with each other, thereby suppressing the expression of one or more of the unreacted phase and the secondary phase in the LLTO composition synthesized in the solid phase in step (iii).
Citation Information
Patent Citations
Secondary battery comprising solid electrolyte layer
KR1020150060584A
Spray-Coated Lithium-Ion Conducting Hybrid Solid Electrolyte For Lithium Battery, Method Of Manufacturing The Same, And Lithium Battery Comprising The Same
KR1020180051716A
